Proceedings of Abu Dhabi International Petroleum Exhibition and Conference 2006
DOI: 10.2523/101717-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Steam-Solvent Processes for the Recovery of Heavy Oil and Bitumen

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractCanada has declining reserves of conventional oil, but vast reserves of heavy oil and bitumen. Over 90% of the world's heavy oil and bitumen trapped in sandstones and carbonates are deposited in Canada and Venezuela. Up to 80% of estimated reserves could be recovered by in-situ thermal operation. The current in-situ thermal technologies such as cyclic steam stimulation (CSS), steam flooding and steamassisted gravity drainage (SAGD) are energy intensive and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…However, the co-injection of butane was found to reduce bitumen production (Orr, 2009). A project managed by Suncor with naphtha co-injection in SAGD in the Firebag area found that naphtha addition has no effect on bitumen production (Nasr and Ayodele, 2006).To achieve a better understanding of ES-SAGD, reservoir simulation was employed to examine the profiles of different reservoir properties, including temperature, gas phase composition, oil phase composition, oil and water saturations, oil viscosity, and oil flow rate in regions near the boundary of the steam chamber. Figures are presented to show important phenomena occurring in those regions and their consequences on oil flow.…”
Section: Introductionmentioning
confidence: 97%
“…However, the co-injection of butane was found to reduce bitumen production (Orr, 2009). A project managed by Suncor with naphtha co-injection in SAGD in the Firebag area found that naphtha addition has no effect on bitumen production (Nasr and Ayodele, 2006).To achieve a better understanding of ES-SAGD, reservoir simulation was employed to examine the profiles of different reservoir properties, including temperature, gas phase composition, oil phase composition, oil and water saturations, oil viscosity, and oil flow rate in regions near the boundary of the steam chamber. Figures are presented to show important phenomena occurring in those regions and their consequences on oil flow.…”
Section: Introductionmentioning
confidence: 97%
“…The minimum specific energy seems to be around 150 kJ/kg, making the process economically affordable. With regard to the separation techniques, both flotation and gravity separation can contribute in providing an appropriate solution to the problem of bitumen concentration, although the performance of flotation seems better for the finest size class (<0.5 mm) of the HERA disintegration product, while gravity concentration can be suggested for the coarser one (0.5-1 mm) according to the indication of the technical literature confirmed by the results of some tentative tests on the Selenice tar sands [4,5,6]. The assessment of the technical and economic feasibility of the concept needs further research including tests of industrial significance extended to samples representative of the local variations of the deposit and of its features as a function of climatic conditions.…”
Section: Discussionmentioning
confidence: 95%
“…A good solvent should be condensed at the same condition with water phase. Hexane is a solvent which has the closest vaporization temperature to steam, which is 215 • C at pressure of 2200 kPa (Nasr et al, 2003;Nasr and Ayodele, 2006). On the other hand, Shu (1984) investigated that mixing of solvents and bitumen will reduce the viscosity drastically at small concentrations of solvents.…”
Section: Introductionmentioning
confidence: 98%